2011
DOI: 10.5539/ijps.v3n1p90
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Self-Concept, Intrinsic Motivation, Self-Determination and Academic Achievement among Chinese Primary School Students

Abstract: The main purpose of this study is to examine the relationship between self-concept, intrinsic motivation and self-determination with academic achievement among the respondents. The sample of the study was 200 students in standard 5 and standard 6 from a Chinese primary school in Johor, Malaysia. Data was collected using a self-developed set of questionnaire. The reliability of the instrument was tested using Cronbach's Alpha and the result was 0.941. The data was analyzed using Statistical Package for Social S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 52 publications
(34 reference statements)
0
15
1
4
Order By: Relevance
“…They reported that students' self-concept influence his/her mathematics learning outcome, because positive view, perception, and his/her confidence will improve mathematics learning outcome. Othman & Leng (2011) reported little different from the previous study. They claimed that students' self-concept relate to his/her academic achievement, but weak.…”
Section: Resultscontrasting
confidence: 83%
“…They reported that students' self-concept influence his/her mathematics learning outcome, because positive view, perception, and his/her confidence will improve mathematics learning outcome. Othman & Leng (2011) reported little different from the previous study. They claimed that students' self-concept relate to his/her academic achievement, but weak.…”
Section: Resultscontrasting
confidence: 83%
“…The study of Othman and Leng (2011) shows that there is a weak significant relationship between selfconcept and academic achievement among the students, a weak and negative significant relationship between students' intrinsic motivation and their academic achievement and a weak significant and negative relationship between students' self-determination and their academic achievement. However, previous studies indicated that academic achievement among students is influenced by several important factors, which directly and indirectly related to self-concept, intrinsic motivation, and self-determination.…”
Section: Respondents' Level Of Self-concept Towards Mathematicsmentioning
confidence: 99%
“…However, it has also been reported that studies in the relevant field dealing with the relationship between academic self-concept and academic achievement are inconsistent (Huang, 2011;Muijs, 1997). The examination of several of these studies (Ahmed & Bruinsma, 2006;Marsh, Byrne, & Yeung, 1999;Othman & Leng, 2011;Papanastasiou & Zembylas, 2004;Saracaloğlu & Varol, 2007;Yahaya, Ramli, Boon, Ghaffar, & Zakariya, 2009;Yıldız, 2010), has resulted in different conclusions, the relationship between academic self-concept and achievement varies depending on the models that deal with this relationship (Green, Nelson, Martin, & Marsh, 2006;Guay, Ratelle, Roy, & Litalien, 2010;Huang, 2011;Marsh & Yeung, 1998;Muijs, 1997).…”
mentioning
confidence: 99%